2020
DOI: 10.3390/pr8010086
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Dynamics Flow Field of Port Plate Pair of an Axial Piston Pump

Abstract: This paper aims at studying the dynamic fluid evolution process of port plate pair of an axial piston pump. First of all, The Renormalization Group k-ε model (RNG k-ε model) is implemented to simulate the dynamic flow distribution and forecast the evolution of the internal vortex structure inside the valve plate chamber with different speeds of pistons and velocities of inlet fluid by using computational fluid dynamics software. Then, an equivalent amplification test model of a piston-valve plate is built up b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Based on the principles of force equilibrium and the composition theorem for concurrent force systems, it can be deduced that the resultant force F o of the reactive force on the cylinder body in the spherical valve train must also pass through the center of the sphere [14].…”
Section: Analysis Of the Load-bearing Mechanism Of Spherical Distribu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the principles of force equilibrium and the composition theorem for concurrent force systems, it can be deduced that the resultant force F o of the reactive force on the cylinder body in the spherical valve train must also pass through the center of the sphere [14].…”
Section: Analysis Of the Load-bearing Mechanism Of Spherical Distribu...mentioning
confidence: 99%
“…Firstly, the overall pump flow field model of the piston pump is established [14,15]. A 20-micrometer oil film structure between the piston chamber (moving structure) and the inlet/outlet channels (stationary structure) is constructed, and the oil film structure is meshed.…”
Section: Modeling the Oil Film Flow Field In The Valve Platementioning
confidence: 99%
“…The mesh density of the fluid model has a significant influence on the calculation results. Only when the mesh number has little effect on the calculation results, the results of numerical simulation are meaningful, so it is necessary to perform mesh independence verification [48,49].…”
Section: Mesh Independence Verificationmentioning
confidence: 99%
“…Quan et al [3] performed an analysis on the flow field of port plate pair of an axial piston pump for different piston speeds and inlet fluid velocities with the use of CFD software. It was found that the scale and strength of vortex reduced with an increase in the piston speed.…”
Section: Papers Presented In the Special Issuementioning
confidence: 99%